Ensaio automatizado de medição da eficiência energética de inversores fotovoltaicos conectados à rede - Bortolini, Ricardo Jochann Franceschi (2018)
The objective of this work is the development of an automated test bench to measure the energy efficiency of grid connected photovoltaic inverters. A detailed study of the energy efficiency measurements standards for photovoltaic inverters with worldwide coverage was carried out, the standards are CEC (California Energy Commission), EN 50530 and IEC 61683. The standards were detailed and compared with each other, regarding the restrictions presented for the tests and equipment used by each of them, such as photovoltaic array simulators, AC grid simulators and measurement equipment. Also, a software for the automation of the tests was developed in LabView® environment to carry out the tests, data acquisition, measurement uncertainties calculation and test report generation.